Speech Act Analysis in Sorong Serah Aji Krama at Sasak Traditional Wedding - Hijriati, Sartika (Lembaga Yasin AlSys, 2021)
Sorong serah aji krama is one of important traditional wedding ceremonies in Lombok, Indonesia. This paper investigated the illocutionary speech acts of Pembayun in sorong serah aji krama at sasak traditional wedding in Bonjeruk village. This study designed as descriptive qualitative research. The data source of this study was collected through video recording, interview, and note-taking. The result of the study shows five types of illocutionary speech acts: assertive, directive, commissive, and expressive. There are no data shows the existence of declarative illocutionary act in this research. Therefore, the percentage of speech act found: assertive 57.14%, directive 14.28%, commissive 4.76%, expressive 23.80%, and declarative 0%.